2018
DOI: 10.1002/jmr.2730
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the inhibition mechanism on HIF‐2 by inhibitor PT2399 and 0X3 using molecular dynamics simulations

Abstract: Targeting transcription factors HIF-2 is currently considered to be the most direct way for the therapy of clear cell renal cell carcinoma. The preclinical inhibitor PT2399 and artificial inhibitor 0X3 have been identified as promising on-target inhibitors to inhibit the heterodimerization of HIF-2. However, the inhibition mechanism of PT2399 and 0X3 on HIF-2 remains unclear. To this end, molecular dynamics (MD) simulations and molecular docking were applied to investigate the effects of 2 inhibitors on struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…For the simulated complex, 500 snapshots were extracted from the last 50 ns along the MD trajectory at intervals of 100 ps. The MM/GBSA [ 47 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ] implemented in AMBER14 [ 78 ], and the electrostatic free energy of solvation (∆G GB ) were calculated by solving GB equations and computing the binding free energies of the complex systems [ 79 ]. The binding energy (ΔG GBTOT ) can be represented as follows: where ΔG GBTOT was obtained by summing the van der Waals (ΔE vdW ) energies and the electrostatic energy (ΔE ELE ) is the sum of polar (ΔG GB ) and nonpolar (ΔG GBSUR ) contributions.…”
Section: Methodsmentioning
confidence: 99%
“…For the simulated complex, 500 snapshots were extracted from the last 50 ns along the MD trajectory at intervals of 100 ps. The MM/GBSA [ 47 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ] implemented in AMBER14 [ 78 ], and the electrostatic free energy of solvation (∆G GB ) were calculated by solving GB equations and computing the binding free energies of the complex systems [ 79 ]. The binding energy (ΔG GBTOT ) can be represented as follows: where ΔG GBTOT was obtained by summing the van der Waals (ΔE vdW ) energies and the electrostatic energy (ΔE ELE ) is the sum of polar (ΔG GB ) and nonpolar (ΔG GBSUR ) contributions.…”
Section: Methodsmentioning
confidence: 99%
“…Co-and chromatin-immunoprecipitation (ChIP) experiments have demonstrated disruption of HIF heterodimer formation and prevention of HRE binding [81]. Although molecular dynamics simulations revealed an interruption of crucial hydrophobic interactions within the HIF-2 dimer for the inhibitors PT2399 and 0X3, this has to be further verified in vivo [82]. State-of-the-art live cell microscopy could further elucidate mechanisms of action.…”
Section: Inhibitors Of Hif-α/β Dimerization and Transcription Complexmentioning
confidence: 99%
“…The most representative HIF-2α-targeted therapies are PT2385 and PT2399 in renal cell carcinoma (12). PT2385 prevents the dimerization of HIF-2α and ARNT/HIF-1β, while PT2399 directly binds to the HIF-2α PAS B domain (11,13). PT2385 was utilized not only in renal cell carcinoma, but also in liver cancer.…”
Section: Hif-2α As An Oncogenementioning
confidence: 99%
“…Currently, the most mature applications involve HIF-2α/VEGF axis-targeted treatments in renal cell carcinoma. HIF-2α inhibitors, such as PT2385 and PT2399, were assessed in phase III clinical trials and were found to be effective for clear-cell renal cell carcinoma treatment (12,13). HIF-2α plays an important role not only in tumours, but also in other diseases.…”
Section: Introductionmentioning
confidence: 99%